Analisis Efektivitas Pelayanan Digital Dan Program Samsat Keliling Dalam Upaya Meningkatkan Kepatuhan Wajib Pajak Kendaraan Bermotor Di UPTD Samsat Serpong - Indri Baqiyatus Sholeha; Khairur Razikin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Regulation of motor vehicle tax (PKB) paying is one of public or government services tasks. One of the public organizations that are directly related to the motor vehicle tax payment service (PKB) is One- Stop Administration System office center (SAMSAT). The phenomenon obtained by the author is the decreasing number of registered motor vehicles as taxpayers, the number differences is quite large from 280,996 in 2019 and 277,996 in 2020. There are unpaid taxes, in the amount of 25,216,985,800 in 2018, 26,938,405,500 in 2019, and 25,814,189,700 in 2020, the motor vehicle unpaid taxes are quite high for these three consecutive years, with the average percentage is 8.53%. This study aims to analyze the effectiveness of digital services and the mobile Samsat program to improve the compliance of motor vehicle taxpayers at the Uptd Samsat Serpong with qualitative descriptive research methods and using interviews, observation, documentation, and triangulation for the data collecting techniques. The results of this study indicate that taxpayer compliance in motor vehicle taxes paying is quite optimal. However, in terms of the motor vehicles payment, there is still no commitment that make there are quite large unpaid taxes every year, and in terms of PKB receipts are not optimal yet even though it’s always reached the target. This is caused by the motor vehicle taxpayers who have not complied with their tax obligations yet. In this case, the difficulties are error that sometimes occurred in the digital service system and the mobile Samsat, and the lack of knowledge for motor vehicle taxpayers who are not active in social media. So, with all of these problems the UPTD Samsat Serpong must be responsive, such as providing a comprehensive socialization and broadening the basis of the taxation system as well as improving the internet network in order to not hinder the motor vehicle taxpayers in carrying out their tax obligations.